Functional investigation of a novel ANKRD11 frameshift variant identified in a Chinese family with KBG syndrome - Shuoshuo Wei; Yanying Li; Wanling Yang; Shuxiong Chen; Fupeng Liu; Mei Zhang; Bo Ban; Dongye He (Heliyon, 2024)
KBG syndrome is a rare autosomal dominant condition characterized by multisystem developmental disorder, primarily caused by loss-of-function variants in ankyrin repeat domain-containing protein 11 (ANKRD11). Approximately 80 % of ANKRD11 variants associated with KBG syndrome, are frameshift and nonsense variants. Current insight into the pathogenesis of KBG syndrome resulting from ANKRD11 truncating variants remains limited. Here, we presented two members from a non-consanguineous Chinese pedigree both exhibiting characteristics fitting the KBG syndrome-associated phenotypic spectrum. Whole-exome sequencing identified a novel heterozygous frameshift variant in ANKRD11 (NM_013275.6, c.2280_2281delGT, p.Y761Qfs*20) in the proband. Sanger sequencing confirmed that the variant was inherited from her mother and co-segregated with KBG syndrome phenotype. In vitro functional assays revealed that the frameshift variant escaped nonsense-mediated mRNA decay, and resulting in a truncated protein with significantly increased expression levels compared to full-length ANKRD11. Immunofluorescence results demonstrated that truncated protein was predominantly expressed in the nucleus of HEK293 cells, while wild-type ANKRD11 was equally distributed in both the nucleus and cytoplasm. Moreover, the truncated protein significantly reduced CDKN1A/P21-promoter luciferase activity in comparison to wild-type ANKRD11 protein, as well as a remarkably decrease in the endogenous CDKN1A/P21 mRNA level in HEK293 cells. These findings suggest a loss of transcriptional activation function and potentially a dominant-negative mechanism. Overall, our study expands the mutational spectrum of ANKRD11 gene and provides new insights into the pathogenic mechanism of KBG syndrome caused by ANKRD11 truncating variants.